Workshop Literasi AI untuk Pembuatan Bahan Ajar Digital bagi Guru SD hingga SMA/SMK - Muhammad Fauzan Gustafi; Amalina Nur Arifah; Muhammad Haedar Zhafran Hidayatulloh (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Digital literacy among educators in Indonesia, particularly regarding the use of Artificial Intelligence (AI) as an instructional tool, remains a critical challenge. This community service program aimed to improve AI literacy and practical skills in creating AI-based digital teaching materials among educators across educational levels, from elementary to senior high school (SD to SMA/SMK). The program was implemented through a series of workshops covering the use of Generative AI, Augmented Reality (AR), and Virtual Reality (VR) in learning design, conducted in Yogyakarta. Participants included 161 educators: 49 junior teachers (experience < 5 years) and 112 senior teachers (experience > 5 years). Data were collected through observation and documented through thematic analysis. Results showed that 100% of junior teachers and 72.32% of senior teachers (81 out of 112) had been exposed to generative AI tools prior to the workshop. Post-workshop evaluations indicated increased understanding of AI tools and improved ability to design AI-integrated teaching materials. Key barriers to AI adoption identified include limited digital infrastructure, low self-efficacy, and absence of structured AI training programs. The primary output of this program is a set of AI-based digital teaching materials produced by participants during the workshop. These findings contribute practical recommendations for designing scalable AI literacy training programs for educators in Indonesia.